2011
DOI: 10.1536/ihj.52.56
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Pressure-Overload Right Ventricular Hypertrophy in Infant Rabbits

Abstract: SummaryAlthough pressure-overload right ventricular hypertrophy is a long-term risk in some congenital heart diseases such as tetralogy of Fallot, how it develops is unclear. The aim of this study was to investigate the mechanism of development of this right ventricular heart failure.Pulmonary artery banding in 10-day-old rabbits induced pressure-overload right ventricular hypertrophy as they grew. Comparisons were made with age-matched sham controls (n = 24 per group). In weekly serial echocardiography, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…The decrease in both myocardial contraction and relaxation after pulmonary banding suggested that the RVH rabbits possess systolic and diastolic dysfunctions. These results are in accordance with previous study in infant rabbits in which the cardiac function impaired beginning at 3 weeks after surgery (Minegishi, Kitahori, Murakami, & Ono, 2011).…”
Section: Functional Remodeling Of the Ventriclesupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in both myocardial contraction and relaxation after pulmonary banding suggested that the RVH rabbits possess systolic and diastolic dysfunctions. These results are in accordance with previous study in infant rabbits in which the cardiac function impaired beginning at 3 weeks after surgery (Minegishi, Kitahori, Murakami, & Ono, 2011).…”
Section: Functional Remodeling Of the Ventriclesupporting
confidence: 93%
“…These results are consistent with previous studies in infant rabbits and adult rats which demonstrated that pulmonary artery banding induced pressure-overload, right ventricular hypertrophy, and apoptosis of the myocytes beginning at 4 weeks after banding and suggested that the apoptosis may lead to myocardial dysfunction (Braun, Szalai, Strasser, & Borst, 2003;Ikeda, Hamada, & Hiwada, 1999;Minegishi et al, 2011;Teiger et al, 1996).…”
Section: Parameterssupporting
confidence: 93%
“…These possibilities will require further investigation but are plausible contributory mechanisms for our observation given the recent reports showing that: (i) the increased right ventricular afterload including that associated with excessive lung inflation can result in cardiomyocyte apoptosis 35,36 ; and (ii) TUDCA appears to also have a beneficial role in pulmonary hypertension 18 . Regardless of the mechanism, we found that UDCA has the potential to preserve CO and mitigate the development of high pulmonary vascular resistance as lung injury develops.…”
Section: Discussionmentioning
confidence: 95%
“…The peak right systolic pressure gradient was calculated from the highest peak velocity using the modified Bernoulli equation [22]. Right ventricular systolic pressure was calculated as the sum of the peak right systolic pressure gradient and the estimated right atrial pressure, which was assumed to be 10 mm Hg based on values from healthy infant rabbits [23,24]. …”
Section: Methodsmentioning
confidence: 99%